The Effect of Psychological Well Being on Work Engagement with Work Ethic as a Mediating Variable - Nining Mustika; Suryani Hardjo; Salamiah Sari Dewi (UNIVERSITAS PAKUAN, 2026)
This research is motivated by the low work engagement of teachers in several private elementary schools in Percut Sei Tuan District, which is suspected to be related to psychological well-being and work ethic. The study aims to analyze the influence of psychological well-being on work ethic and work engagement, as well as to test the mediating role of work ethic. The study used a quantitative approach with an explanatory research type. Primary data were obtained through a Likert scale that measures psychological well-being, work ethic, and work engagement in private elementary school teachers, then analyzed using Confirmatory Factor Analysis, path analysis, and the Sobel test. The results showed that psychological well-being significantly influences work ethic and work engagement, and work ethic mediates the relationship. These findings emphasize the importance of psychological well-being in improving teacher professional engagement.